The science in Islamic perspective - Muslimah , Muslimah; Hamdanah , Hamdanah; Nina , Nina (International research journal of management, IT and social sciences, 2020)
This study aimed to discuss the importance of science and the Islamic perspective’s position controller. The data collection of this research was carried out using the library method. Therefore, it is included in library research, preceded by collecting printed and electronic references, sourced from books and articles relating to the meaning, scope, and position of knowledge. We continued to review and explore the connections. The results explain the importance of science from the perspective of Islamic studies, namely that it cannot be separated between human life and progress/civilization. In this context, science and technology are among the branches of knowledge that provide great benefits and benefits to human survival in this world and the hereafter. Islam has glorified people who master science. Even since the Prophet Muhammad was sent to become a prophet, he always exemplified and reminded him to strive for it because he expected Allah SWT’s pleased.